Anorectal malformations - Ajay Narayan Gangopadhyay; Vaibhav Pandey (Wolters Kluwer Medknow Publications, 2015)
Anorectal malformations (ARMs) are among the more frequent congenital anomalies encountered in paediatric surgery, with an estimated incidence ranging between 1 in 2000 and 1 in 5000 live births. Antenatal diagnosis of an isolated ARM is rare. Most cases are diagnosed in the early neonatal period. There is a wide spectrum of presentation ranging from low anomalies with perineal fistula having simple management to high anomalies with complex management. Advances in the imaging techniques with improvement in knowledge of the embryology, anatomy and physiology of ARM cases have refined diagnosis and initial management. There has been marked improvement in survival of such patient over the last century. The management of ARM has moved forward from classical procedures to PSARP to minimal invasive procedures. But still the fecal and urinary incontinence can occur even with an excellent anatomic repair, mainly due to associated problems. There has been a paradigm shift in approach to these patients which involves holistic approach to the syndrome of Anorectal malformations with a long term goal of achievement of complete fecal and urinary continence with excellent quality of life.